Analisis Kesalahan Peserta Didik Kelas X SMK Dalam Menyelesaikan Soal Pemecahan Masalah Berdasarkan Tahapan Kastolan - Suci Aisyah Putri; Edwin Musdi (Universitas PGRI Madiun, 2021)
Mathematics is one of the important subjects to improve the mathematical problem solving ability of Vocational High School (SMK) students. However, there are still many who make mistakes when solving problem solving problems. The purpose of this article is to describe student errors in solving problem solving problems based on the Kastolan stages. This type of research is descriptive qualitative research. Data collection techniques in this study were written tests and field notes. The research subjects were students of class X SMK. The results of this study indicate that there are 3 types of errors made by students in solving problem solving problems according to the Kastolan stages, namely (1) conceptual errors, there are 42% of students who make this error; (2) procedural errors, 28% of students made this mistake; and (3) technical errors, there are 33% of students who make mistakes.